EVALUASI TINGKAT KEPUASAN BENDAHARA TERHADAP PELAYANAN KEUANGAN DAERAH: STUDI PADA BPKAD KABUPATEN PEGUNUNGAN ARFAK - Towansiba, Margaretha; Heatubun, Febianus; Rahaded, Lucia Klamensia (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to evaluate the satisfaction level of treasurers with the services provided by the Regional Financial and Asset Management Agency (BPKAD) of Pegunungan Arfak Regency as an indicator of public service performance in regional financial management. High-quality public service reflects the success of bureaucratic reform and the professionalism of civil servants in implementing transparent, accountable, and user-oriented financial governance. This research employs a descriptive qualitative approach with a population of 92 treasurers and a sample of 48 respondents, determined using the Slovin formula with a 10 percent margin of error. Data were collected using the Community Satisfaction Survey (SKM) instrument in accordance with Ministerial Regulation of PANRB Number 14 of 2017, which assesses nine key aspects of public service quality. The findings reveal a Community Satisfaction Index (IKM) score of 79.9, categorized as good, with the highest ratings on the aspects of staff behavior and competence, while complaint handling received the lowest score. These results indicate that BPKAD’s service delivery is generally effective yet still requires improvement in communication mechanisms and responsiveness to user feedback. The study highlights the importance of strengthening human resource capacity, promoting digital-based service innovations, and developing an integrated online complaint system as strategic efforts to enhance public service quality within the local government of Pegunungan Arfak Regency.